A Study of Child Abuse in Arundhati Roy’s The God of Small Things: Exploring Child Abuse in Arundhati Roy's Novel (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Child abuse is the physical, sexual, emotional mistreatment or neglect of a child. In the United State the Centers for Disease Control and Prevention (CDC) define child maltreatment as any act or series of acts of commission or omission by a parent or other caregiver that results in harm, potential for harm or threat of harm to a child. Child abuse can occur in a child’s home or in the organizations, schools or communities the child interact with. There are four major categories of child abuse: neglect, physical abuse, psychological/emotional abuse and child sexual abuse.Different jurisdictions have developed their own definitions of what constitutes child abuse for the purpose of removing a child from his/her family and/or prosecuting a criminal charge. According to The Journal of Child Abuse and Neglect:Child abuse is any recent act or failure to act on the part of parent or caretaker which results in death, serious physical or emotional harm, sexual abuse or exploitation, an act or failure to act which present and imminent risk of serious harm. (Herrenkohl, 2005)